N-terminal acetylation of a mastoparan-like peptide enhances PE/PG segregation in model membranes - Miasaki, Kenneth M.F. [UNESP] (2020)
The synthetic peptides L1A and its acetylated analog (acL1A) display potent Gram-negative bactericidal activities without being hemolytic. We have gathered evidence that the N-terminal acetylation of L1A enhances the lytic activity in anionic vesicles with high capability to insert into and disturb lipid packing of model membranes. Here, the impact of L1A and acL1A was evaluated on a model membrane that mimics the cytoplasmic membrane of Gram-negative bacteria, which is rich in phosphatidylethanolamine (PE) and phosphatidylglycerol (PG), using 3:1 mixture of POPE/DOPG and a variety of techniques. We followed peptide adsorption and penetration by zeta potential determination of large unilamellar vesicles, accessibility of tryptophan residue to acrylamide by quenching assays, and Gibbs isotherms. The secondary structure of the peptide on the membranes was assessed using circular dichroism. Peptide mixing ability with the lipids and phase segregation was assessed by the observation of Langmuir monolayers with fluorescence microscopy, as well as with differential scanning calorimetry thermograms of multilamellar vesicles. All in all, the results indicate that both peptides adsorb and penetrate POPE/DOPG membranes with similar affinities, decreasing the surface charge, and adopting alpha structures. Both peptides mix with DOPG and demix from POPE, and consequently, persist at the interface to larger surface pressures in the presence of PG than in pure PE monolayers. This selective degree of mixing of the peptides with PE and PG leads to peptide-induced segregation of PG from PE, being the less charged peptide, acL1A, able to segregate the lipids more efficiently.